Revisiting the blurring practices between editorials and advertising - Dix, Steve; Phau, Ian (School of Marketing, Curtin Business School, 2008)
This study aims to compare the perceptions of agencies, advertisers and media consumers on the blurring practices commonly used to confuse editorial and advertising. The findings did not substantiate the concerns that the blurring content is misleading to the players in the industry. Advertisers and agencies showed significantly positive attitudes towards blurring practices. It is also revealed that there are little significant differences for the attitudes towards regulation of blurring practices between the three sample groups. However, there are differences in perception across sample groups towards the specific blurring practices. Further managerial implications were provided to better allow advertisers and agencies a guide to shifts in the perceived role of blurring practices in advertising across a fifteen year period.